Urban resilience – an attempt to characterise the concept - Wałachowski, Karol (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2022)
The concept of resilience is becoming one of the most popular approaches in modern science. Its popularity is influenced by the unpredictability of the modern VUCA world. It is no different in urban science. The urban resilience is currently making its way from a strictly academic concept to a viable approach in public policies. The aim of this paper is to describe the concept of urban resilience. The specific objectives are: (1) to identify the definition of the resilient city according to the most cited authors, (2) to present the main ways of understanding the concept, (3) to compare resilience with the concepts of sustainability and competitiveness, (4) to identify factors of resilience in relation to urban development, and (5) to analyse the occurrence of the concept of resilience in contemporary urban policies. The method used is a review of scientific literature, recommendations of international institutions and strategic documents. The paper proves that resilience is dynamically increasing its popularity, both among scientific research and strategic documents. Nevertheless, a disadvantage of the concept is the current high conceptual blurring, which prevents effective comparative research and the creation of general recommendations.